The Macrophage Response Is Driven by Mesenchymal Stem Cell-Mediated Metabolic Reprogramming - Luque-Campos, Noymar; Bustamante-Barrientos, Felipe A.; Pradenas, Carolina; García, Cynthia; Araya, María Jesús; Bohaud, Candice; Contreras-López, Rafael; Elizondo-Vega, Roberto; Djouad, Farida; Luz-Crawford, Patricia; Vega-Letter, Ana María (Frontiers in Immunology, 2021)
Mesenchymal stem cells (MSCs) are multipotent adult stromal cells widely studied for their regenerative and immunomodulatory properties. They are capable of modulating macrophage plasticity depending on various microenvironmental signals. Current studies have shown that metabolic changes can also affect macrophage fate and function. Indeed, changes in the environment, prompting phenotype change. Therefore, in this review, we will discuss how MSCs orchestrate macrophage’s metabolic plasticity and the impact in their function. An improved understanding of the crosstalk between macrophage and MSCs will improve our knowledge of MSC’s therapeutic potential in the context of inflammatory diseases, cancer, and tissue repair processes in which macrophage are pivotal.